FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT GENERASI Y DAN Z BERWAKAF UANG MELALUI DIGITAL BANKING SYARIAH - Nur Syifa, Dina; Pimada, Laila Masruro (Islamic Economics and finance in Focus, 2023)
Indonesia has a large potential for cash waqf, which is 188 trillion annually, but the accumulation that has been successfully collected has only touched 831 billion if it is only 0.5 percent of its total potential. The presence of digitalization is expected to be able to increase the intention of generations Y and Z who dominate the demographics of Indonesian society and are the closest to using digital technology. Purpose of this study is to find out what factors can affect generations Y and Z in performing cash waqf through digital banking of sharia banks. This study used a quantitative method with the SEM-PLS analysis tool. The results from this study indicate trust and social influence is a factor that has a significant influence on intention, while knowledge and perception of convenience do not have a significant influence on the intention of generations Y and Z in performing cash waqf through digital banking of sharia banks. This research is expected to be a basis for policy makers in formulating a cash waqf collection strategy in the digitalization era and can be a reference for future research.